A multi-institutional analysis of prehospital tourniquet use. Issue 1 (July 2015) - Schroll, Rebecca; Smith, Alison; McSwain, Norman E.; Myers, John; Rocchi, Kristin; Inaba, Kenji; Siboni, Stefano; Vercruysse, Gary A.; Ibrahim-zada, Irada; Sperry, Jason L.; Martin-Gill, Christian; Cannon, Jeremy W.; et al.
Abstract : BACKGROUND: Recent military studies demonstrated an association between prehospital tourniquet use and increased survival. The benefits of this prehospital intervention in a civilian population remain unclear. The aims of our study were to evaluate tourniquet use in the civilian population and to compare outcomes to previously published military experience. We hypothesized that incorporation of tourniquet use in the civilian population will result in an overall improvement in mortality. METHODS: This is a preliminary multi-institutional retrospective analysis of prehospital tourniquet (MIA-T) use of patients admitted to nine urban Level 1 trauma centers from January 2010 to December 2013. Patient demographics and mortality from a previous military experience by Kragh et al. ( Ann Surg. 2009;249:1–7) were used for comparison. Patients younger than 18 years or with nontraumatic bleeding requiring tourniquet application were excluded. Data were analyzed using a two-tailed unpaired Student's t test with p < 0.05 as significant. RESULTS: A total of 197 patients were included. Tourniquets were applied effectively in 175 (88.8%) of 197 patients. The average Injury Severity Score (ISS) for MIA-T versus military was 11 ± 12.5 versus 14 ± 10.5, respectively ( p = 0.02). The overall mortality and limb amputation rates for the MIA-T group were significantly lower than previously seen in the military population at 6 (3.0%) of 197 versus 22 (11.3%) of 194 ( p = 0.002) and 37 (18.8%) of 197 versus 97 (41.8%) of 232 ( p = 0.0001), respectively. CONCLUSION: Our study is the largest evaluation of prehospital tourniquet use in a civilian population to date. We found that tourniquets were applied safely and effectively in the civilian population. Adaptation of this prehospital intervention may convey a survival benefit in the civilian population. LEVEL OF EVIDENCE: Epidemiologic study, level V.